Toxicity of fipronil to Folsomia candida in contrasting tropical soils and soil moisture contents: effects on the reproduction and growth - Hennig T.B.* (2022)
© 2021, The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.This study assessed the influence of three tropical soil types and soil moisture content on the toxicity and risk of the insecticide fipronil to collembolans Folsomia candida. Chronic toxicity tests were performed in a Tropical Artificial Soil (TAS), an Oxisol and an Entisol spiked with increasing concentrations of fipronil to assess the effects on the reproduction and growth of the species. The soil moisture contents were kept at 60% (standard condition) and 30 or 45% (water restriction) of their water holding capacity (WHC). The toxicity of fipronil on collembolans reproduction was about three times higher in Entisol compared to TAS or Oxisol. Higher toxicities were also found in the drier TAS (EC50 30%WHC = 0.20 vs EC50 60%WHC = 0.70 mg kg−1) and Oxisol (EC50 45%WHC = 0.27 vs EC50 60%WHC = 0.54 mg kg−1), while in Entisol lower impacts were found in the drier samples (EC50 30%WHC = 0.41 vs EC50 60%WHC = 0.24 mg kg−1). For all tested soils, the size of generated collembolans was reduced by the fipronil concentrations, regardless of soil moisture. However, the drier condition increased the effect on the growth in TAS and Entisol for some concentrations. A significant risk of exposure was found in TAS and Oxisol at drier conditions and, for Entisol, regardless of the soil moisture. The toxic effects and risk of fipronil on collembolans were higher in the natural sandy soil. The soil moisture content increase or decrease the toxicity of the insecticide for collembolans, depending on soil type.